ILEGAL COASTAL DEVELOPMENT AND ITS ENVIRONMENTAL IMPACTS: POLICY CHALLENGES IN VILLA CONSTRUCTION ALONG DEN CARIK BEACH, BULELENG - Holy, Ni Kadek Principia Pristine (Universitas Pendidikan Ganesha, 2025)
The illegal construction of villas along the coastal area of Den Carik Beach, Buleleng Regency, presents a critical challenge in spatial planning, environmental protection, and law enforcement. These unauthorized developments have caused significant ecological degradation, disrupted coastal ecosystems, and restricted public access to coastal spaces. This paper normatively analyzes the legal and policy implications of such unlawful development and examines the regulatory challenges in achieving sustainable coastal management. Employing a normative legal approach through literature-based analysis, this study reviews relevant statutory provisions, including Law No. 26 of 2007 on Spatial Planning, Law No. 27 of 2007 in conjunction with Law No. 1 of 2014 on the Management of Coastal Areas and Small Islands, and regional regulations applicable in Buleleng Regency. The findings indicate that the lack of legal enforcement, weak regulatory oversight, and overlapping authorities are the main contributing factors to continued violations in coastal zones. This article recommends the reform of the legal and institutional framework, including regulatory harmonization between national and regional laws, strengthening administrative supervision, and increasing accountability in the permitting process. Furthermore, the study underscores the importance of embedding ecological justice and environmental sustainability as fundamental principles in coastal development policies, especially in areas where ecological function intersects with tourism value.